(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This paper examines the unique challenges and opportunities faced by engineering leaders in a globalized world. The research will explore issues such as cultural differences, communication barriers, and virtual team management. The paper will also discuss the potential benefits of a globalized workforce, such as access to diverse skillsets and increased creativity. The study will propose strategies for effective leadership in a globalized engineering environment.